2008
DOI: 10.1111/j.1471-6712.2007.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience of being the spouse/cohabitant of a person with bipolar affective disorder: a cumulative process over time

Abstract: The aim of the study was to identify and describe spouses'/cohabitants' experiences of living with a partner with bipolar affective disorder over time. Qualitative research interviews were conducted with eight spouses/cohabitants. Transcribed interviews were analysed structurally based on Ricoeur's phenomenological hermeneutics as described by Lindseth and Norberg. The participants' shared lives ranged from 6 to 51 years, and the study found three major aspects that characterized their experience along this ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 36 publications
5
84
0
4
Order By: Relevance
“…These outcomes (especially first and second conclusions) agree with those obtained by Janowsky and his colleagues (1970), but also by Tranvåg and Kristoffersen (2008), who showed that manic behaviour (associated with BD I) had a great impact on functioning of marriage and spousal burden. What is interesting, bipolar I disorder is associated with a lower likelihood of men getting married (Lieberman et al 2010).…”
Section: Discussionsupporting
confidence: 81%
“…These outcomes (especially first and second conclusions) agree with those obtained by Janowsky and his colleagues (1970), but also by Tranvåg and Kristoffersen (2008), who showed that manic behaviour (associated with BD I) had a great impact on functioning of marriage and spousal burden. What is interesting, bipolar I disorder is associated with a lower likelihood of men getting married (Lieberman et al 2010).…”
Section: Discussionsupporting
confidence: 81%
“…In a more recent study by Tranvag and Kristoffersen (2008), they concur that the negative experiences of those affected by mental illness can lead to new understanding through the process of grief, acceptance and reconciliation. Dyer and McGuiness (1996) go on to say that at least one caring individual to validate a person's worth is needed help develop resilience during adversity.…”
Section: Methodsmentioning
confidence: 90%
“…In a more recent study, Tranvag and Kristoffersen (2008, p. 12) found family members "experienced a mixed feeling of uncertainty, powerlessness and hope" (Tranvag & Kristoffersen, 2008, p. 12). However, Tranvag and Kristoffersen (2008) found that the more positive aspects of the caregiving experience emerged over time including acceptance, reconciliation and hope. This finding is supported in an earlier study of male caregivers of mentally ill relatives who also "expressed improvement in role development over time" (Mays & Lund, 1999, p. 24).…”
Section: Mental Illness and The Family Experiencementioning
confidence: 95%
See 1 more Smart Citation
“…Research into the situation of relatives living with someone with an SMI reveals how vulnerable that position is. A spouse or partner who bears the responsibility for the household and the children, may feel taken advantage of by psychiatric services if they find they have to care for their seriously mentally ill counterpart with no outside help (Ostman 2000;Ostman and Hansson 2004;Tranvåg and Kristoffersen 2008). As a result, the responsibility placed on the healthy member of the household can be overwhelming and the burden may result in such individuals having their own psychiatric problems (Wittmund et al 2002).…”
Section: Supporting Parents With Smimentioning
confidence: 99%